1985
DOI: 10.3109/01485018508988293
|View full text |Cite
|
Sign up to set email alerts
|

Properties and Regulation of GnRH Receptors in the Anterior Pituitary and the Testis of the Rat: Different Response of Leydig Cell LH and GnRH Receptors to Hormonal Treatments

Abstract: The properties (association and dissociation rates, affinity and specificity) of GnRH receptors in the rat pituitary and the Leydig cells are very similar. In addition, in vivo administration for 5 or 11 days of 10 micrograms of GnRH to adult rats resulted in an increase (p less than 0.01) in both Leydig cell and pituitary GnRH receptors. In contrast, the same treatment caused a significant decrease (p less than 0.01) of Leydig cell LH receptor number. Furthermore, testosterone propionate (500 micrograms/day),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
0
5
0
Order By: Relevance
“…Studies using rats have most commonly demonstrated that the levels of GnRH-R and GnRH-R gene expression are reduced by androgen treatment (18)(19)(20). However, this does not appear to be the case in the mouse.…”
Section: Discussionmentioning
confidence: 90%
See 2 more Smart Citations
“…Studies using rats have most commonly demonstrated that the levels of GnRH-R and GnRH-R gene expression are reduced by androgen treatment (18)(19)(20). However, this does not appear to be the case in the mouse.…”
Section: Discussionmentioning
confidence: 90%
“…In addition to modulating the activin/FS system in the pituitary, androgens have been shown to regulate GnRH sensitivity via alterations in the level of GnRH-Rs (16)(17)(18)(19)(20). In fact, in the case of the LH␤ gene, GnRH stimulation was required to observe androgen repression in the L␤T2 cell model (9,10).…”
Section: Androgen Enhances Gnrh Stimulation Of Fsh␤ Gene Expressionmentioning
confidence: 96%
See 1 more Smart Citation
“…Indeed, these receptors have been shown to elicit signals central to the growth and development, maintenance and normal functioning, as well as the degeneration of the brain. At the present time, it is difficult to determine whether the effects ascribed to a particular HPG hormone with regard to neuronal structure and function are mediated via its own receptor signaling, or via feedback regulation on other HPG hormone receptors; such is the case for estrogen modulation of GnRH, gonadotropin and progesterone receptor expression in neuronal cells [124,139,153]. Likewise, it is not clear to what extent the above cognitive and functional observations are due to one hormone per se (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Negative feedback of gonadal steroids and inhibin at the hypothalamus and anterior pituitary gland was thought to be the primary regulator of gonadotropin secretion in pigs (Ford, Klindt, & Wise, ). Neuropeptides and their receptors are also expressed in the gonad, and can directly affect gonadal function (Iwashita & Catt, ; Jegou, Brekke, Naess, Torjesen, & Hansson, ; Kakar, Musgrove, Devor, Sellers, & Neill, ; Nikula & Huhtaniemi, ; Petersson, Emons, & Hammar, ); however, information indicating that neuropeptides may act as paracrine regulators of testicular function in the boar is lacking. Here, we review and present evidence that RFamide peptides, the products of the NPVF gene, are not major hypophysiotropic hormones in the pig, but could be important paracrine factors in the negative regulation of testosterone secretion in boars.…”
Section: Introductionmentioning
confidence: 99%